Dynamics of single Fe atoms in graphene vacancies. - Robertson, A; Montanari, B; He, K; Kim, J; Allen, C; Wu, Y; Olivier, J; Neethling, J; Harrison, N; Kirkland, A; Warner, J (2013)
Focused electron beam irradiation has been used to create mono and divacancies in graphene within a defined area, which then act as trap sites for mobile Fe atoms initially resident on the graphene surface. Aberration-corrected transmission electron microscopy at 80 kV has been used to study the real time dynamics of Fe atoms filling the vacancy sites in graphene with atomic resolution. We find that the incorporation of a dopant atom results in pronounced displacements of the surrounding carbon atoms of up to 0.5 Å, which is in good agreement with density functional theory calculations. Once incorporated into the graphene lattice, Fe atoms can transition to adjacent lattice positions and reversibly switch their bonding between four and three nearest neighbors. The C atoms adjacent to the Fe atoms are found to be more susceptible to Stone-Wales type bond rotations with these bond rotations associated with changes in the dopant bonding configuration. These results demonstrate the use of controlled electron beam irradiation to incorporate dopants into the graphene lattice with nanoscale spatial control.